(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Taila Kalpana- A liquid dosage form of Ayurveda used for both external and internal application, has an important role in clinical practice. Asanavilwadi taila is a preparation mentioned in Sahasrayogam taila prakaranam and in Chikitsa manjari Siro roga chikitsa. It is used in the treatment of diseases of eye, ear and head and found to be very effective. Based on the data collected about the production of Asanavilwadi tailam from various manufacturing companies, it was noted that large amount of Asanavilwadi tila tailam and Asanavilwadi kera tailam are produced. In the present scenario there is increase in the number of manufacturing companies, increased production of formulations and there is decreased availability of raw drugs. So, it is necessary to confirm the genuinity of formulations available in the market. But Asanavilwadi tailam has not been standardized yet in API. This work was initiated to develop a standard analytical parameter for Asanavilwadi tila tailam and Asanavilwadi kera tailam. Asanavilwadi taila is prepared both in the media of Tila taila and Kera tailam as both samples are used for clinical practice and physico-chemical analyses were done. Standard analytical protocol proposed by Pharmacopoeial Laboratory of Indian Medicine (PLIM) and Ayurvedic Pharmacopoeia of India were taken as the study tool.